PENGEMBANGAN SISTEM INFORMASI DENGAN METODE AGILE DEVELOPMENT YANG SEARAH DENGAN RANCANGAN STRATEGIS IT/IS PADA PERUSAHAAN - Hoga Saragih; Teddy Sutanto (SISFOTENIKA, 2013)
Abstract: In entering the business competition lately, especially in restaurant industry can’t be separated from the role of information technology / information systems. In an information systems development there is two method that can be used , that waterfall and agile development. In this opportunity we believe that systems development with agile development method will bring more success for an information systems development project. This method was chosen because we undertook information system strategic planning in a company which is a family business. System information with agile development that aligns with corporate strategic planning should have always controlled, and where there is crafting strategy then move quickly the information systems development is expected to adapt. Keywords: Information Systems, Technology Information, Agile development, family business.